Technology Innovations for Behavioral Education
XVII, 72 p.
Keywords: Technology Innovations for Behavioral Education Mary Gregerson, editor Evolving alongside technological advances is a new generation of tech-savvy, media-attuned students, particularly in graduate and medical programs. But while much is being made of a growing digital divide between teachers and learners, inventive instructors are using the new electronic media to design educational strategies that are creative and practical, engaging and effective. Technology Innovations for Behavioral Education documents these successful strategies emphasizing both technology-powered breakthroughs and psychology-driven instructional techniques reflecting the quantum leap in how students learn and what they have come to expect in the classroom. In these pages, multimedia pedagogy in itself involves multitasking, as competency development encourages technological development and improvements in health care education translate into improvements in client care. Chapters explore leading-edge uses of technology and examine foundational issues of critical value to working in new-media contexts, including: A virtual-classroom approach to culturally responsive health care. Film as a mass media model for health-promoting behaviors. Training for telemental health care: bridging technology, clinical, and outreach competencies. New technology as tools in professional development. Research techniques for locating high-quality mental health information on the Web. Ethical and legal issues in media psychology. Technology Innovations for Behavioral Education is inspiring reading for educators and graduate students in post-graduate education like medicine, public health, and mental health. This text is a primer for learning this burgeoning field and an idea book for making the most of itspotential. .